Digital transformation of construction enterprises and carbon emission reduction: evidence from listed companies - Zhao, Sanglin; Deng, Hao; Cao, Jikang; Gustaf, Måns (Frontiers in Environmental Science, 2025)
As a key sector for energy consumption and carbon emissions, the construction industry’s carbon reduction measures have important strategic significance for achieving the “dual carbon” goals. Based on data from Chinese listed construction companies from 2000 to 2021, this study empirically explores the effects and pathways of digital transformation on carbon reduction. The results indicate that digital transformation can significantly reduce the carbon emission intensity of enterprises, mainly through promoting green technology innovation, improving total factor productivity, and optimizing production processes and business structures. Heterogeneity analysis shows that digital technology has a more significant emission reduction effect on highly competitive enterprises in the industry, and there are significant differences in carbon emission reduction between regions. This study provides a reference for carbon neutrality pathways in the field of architecture.